Thrombotic Microangiopathy Associated with Gemcitabine in Non-Small Cell Lung Cancer: A Case Report - Tadahiro Kuribayashi (Karger Publishers, 2021)
A 69-year-old man with refractory lung adenocarcinoma was treated with gemcitabine and vinorelbine. Dyspnea and hypertension developed after the 17th cycle of chemotherapy. Laboratory findings revealed intravascular hemolysis and renal dysfunction. Thrombotic microangiopathy (TMA) was confirmed by renal biopsy. Antihypertensive and steroid therapies were ineffective. After plasmapheresis, intravascular hemolysis and renal dysfunction gradually improved. However, the disease progressed, and he died 6 months after TMA diagnosis. Autopsy revealed similar pathological findings to those of the renal biopsy. It is important to discontinue gemcitabine at the onset of TMA and consider TMA when using gemcitabine for long periods.